Elucidating the role of SHROOM4 in non-small cell lung cancer: expression patterns, clinical correlations, and potential functions - Zhang, Yuqi; Qiang, Rong; Ding, Mengyang; Wang, Lin (Frontiers in Immunology, 2026)
BackgroundLung cancer remains the leading cause of cancer-related mortality worldwide, with non-small cell lung cancer (NSCLC) being the most common type. SHROOM4, a protein integral to cytoskeletal organization and cellular signaling, has not been extensively studied in NSCLC.MethodsThrough bioinformatics analysis of public databases, we investigated the expression of SHROOM4 and its relationship with clinical outcomes and potential mechanism. And we validated the mRNA and protein expression of SHROOM4 in lung squamous cell carcinoma (LUSC) tissues and corresponding normal tissues.ResultsOur analysis demonstrated a notable downregulation of SHROOM4 mRNA and protein expression, along with its high diagnosis capability in lung cancer, especially pronounced in LUSC, Additionally, higher levels of SHROOM4 were linked to worse clinical outcomes in lung cancer, characterized by reduced survival and more advanced disease stages. Single-cell RNA-seq data and differential analysis show SHROOM4’s high expression in stromal cells and its association with angiogenesis and Wnt/Beta-Catenin pathways possibly through ANGPTL7/SFTPC. Meanwhile, SHROOM4 was found to co-express with PTPN13/CACNA1C impacting the tumor microenvironment (TME) and to participate in critical signaling pathways like cell circle and WNT. Moreover, positive correlations were discovered between SHROOM4 expression and immune infiltration scores in NSCLC.ConclusionThese results underscore the potential of SHROOM4, an anticancer role, as both a diagnostic and therapeutic target, particularly in LUSC. And SHROOM4 may modulate NSCLC progression by affecting the TME in many ways. Further studies are essential to elucidate SHROOM4’s role in lung cancer progression and to validate its clinical utility.